Non-Destructive Model for Estimating Leaf Area and Growth of Cnidoscolus aconitifolius Cultivated Using Different Stem Diameter of the Semi Hardwood Cuttings - Fitra Gustiar; Benyamin Lakitan; Dedik Budianta; Zaidan P. Negara (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2023)
Chaya (Cnidoscolus aconitifolius (Mill.) I.M. Johnst.) is a perennial leafy vegetable. Since the leaf blade is the most crucial component of the Chaya, it should be advantageous to estimate the leaf area non-destructively.Â This research aimed to (a) develop a beneficial non-destructive model for leaf area estimation, and (b) ascertain the impact of stem cutting diameter when used as planting material on chaya growth rate. The results demonstrated that utilizing the length x width (LW) of the middle lobe as the predictor and the zero intercepts linear regression LA = 1.679 LW with R2=0.947 determination coefficient was the most dependable model for Chaya plant leaf area estimation. The stem diameter, which ranged from 9.9 to 17.3 mm, had affected the shoot length, number of leaves, and canopy area between 5 and 7 weeks after planting (WAP). The variations in growth metrics diminished along with the age of plants. The diameter of the stem cutting used as planting material had no effect on the fresh weight of young edible shoot tip at 11 WAP. On Chaya plants that were cultivated with larger stem cutting diameters, the fresh leaf weight at the branch tips was heavier.